2019
DOI: 10.1177/0308575919841752
|View full text |Cite
|
Sign up to set email alerts
|

‘They don’t meet the stereotypes in the boxes…’: Foster carers’ and clinicians’ views on the utility of psychometric tools in the mental health assessment of looked after children

Abstract: Background: Looked-after children (LAC) frequently experience greater mental health challenges than the general child population. There has been a call for greater focus on early preventative interventions and priority access to specialist mental health support for this population. Brief mental health screening tools often provide the gateway to services and yet there is a lack of suitable assessment tools available for LAC. The current study is the first to explore the perspectives of foster carers and CAMHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…This result contributes to making professionals more aware of the actual mechanisms that lead to problematic behavior in adolescents, which should be targeted in early interventions (Lacey & Minnis, 2020). Thus, neglecting the presence of trauma-related symptoms may entail an inaccurate assessment of the needs of adolescents in residential care and, therefore, a reduction in the allocation of resources for trauma-informed interventions (Frogley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This result contributes to making professionals more aware of the actual mechanisms that lead to problematic behavior in adolescents, which should be targeted in early interventions (Lacey & Minnis, 2020). Thus, neglecting the presence of trauma-related symptoms may entail an inaccurate assessment of the needs of adolescents in residential care and, therefore, a reduction in the allocation of resources for trauma-informed interventions (Frogley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of consensus about how best to formulate and manage the mental health needs of these children. Our own experience, supported by the empirical literature and clinical commentaries, [1][2][3][4][5] suggests that there can be considerable reluctance to use standard assessment protocols and diagnostic frameworks when formulating the needs of this group of young people. Whilst some children in the welfare system may experience significant emotional distress and functional impairment yet not meet current diagnostic thresholds, multiple reviews have shown that almost half of children in the welfare system do meet criteria for a diagnosable mental health disorder [6,7] .…”
mentioning
confidence: 99%